Reconstructing atmospheric circulation over southern New Zealand: Establishment of modern westerly airflow 5500 years ago and implications for Southern Hemisphere Holocene climate change. (1st March 2017) - Turney, C.S.M.; Wilmshurst, J.M.; Jones, R.T.; Wood, J.R.; Palmer, J.G.; Hogg, A.G.; Fenwick, P.; Crowley, S.F.; Privat, K.; Thomas, Z.
Abstract: Late-twentieth century changes in the intensity and migration of Southern Hemisphere westerly winds have been implicated in spatially complex variability in atmospheric and ocean circulation, and ice-sheet dynamics, across the mid- to high-latitudes. A major uncertainty, however, is whether present day hemispheric-wide symmetrical airflow is representative of past behaviour. Here we report a multi-proxy study from Stewart Island and southern Fiordland, New Zealand (46–47°S) reconstructing Holocene changes at the northern limit of westerly airflow. Increased minerogenic input and a pronounced shift in cool-loving vegetation around 5500 years ago is consistent with the establishment of westerly airflow at this latitude in the southwest Pacific. In marked contrast, stronger winds are reported further south over the subantarctic Auckland (50°S) and Campbell (52°S) Islands from 8000 years ago. Intriguingly, reconstructions from the east Pacific suggest a weakening of core westerly airflow after 8500 years ago, but an expansion along the northern limits sometime after 5500 years ago. Our results suggest similar atmospheric circulation changes have been experienced in the Pacific since 5500 years ago, but indicate an expanded network of sites is needed to comprehensively test the driver(s) and impact(s) of Holocene mid-latitude westerly winds across the Southern Hemisphere. Highlights: Southern Hemisphere mid-latitude westerlies play global role in climate-ice dynamics. Limited number of Holocene records of atmospheric circulation. New Zealand's Stewart Island lies at northern limit of westerly airflow. Wind-blown sediments and vegetation capture strengthening circulation 5500 years ago. Our result imply establishment of 'modern' hemispheric circulation in mid-Holocene.